Pre-school practitioners, child poverty and social justice. Issue 5 (8th June 2015) - Simpson, Donald; Lumsden, Eunice; McDowall Clark, Rory
Abstract : Purpose: – Several ideas exist about social justice and how inequalities can be tackled to help families and children in poverty. The Coalition government released the UK's first Child Poverty Strategy in 2011. Pervaded by neoliberal ideology, the strategy mentions "empowering" pre-school services and practitioners within the childcare market "to do more for the most disadvantaged" (Department for Work and Pensions (DWP) and Department for Education (DfE) 2011, p. 35). The purpose of this paper is to bring to light how Early Childhood Education and Care (ECEC) practitioners across England have engaged with policy discussions and adopted expectations concerning their place in addressing child poverty. Design/methodology/approach: – Using a phenomenological qualitative research design the paper draws upon 30 interviews with pre-school practitioners in three geographic areas of England. All interviewees worked with families and children in poverty and were senior ECEC practitioners within their pre-school settings. Findings: – Many interviewees shared the Coalition's construction of child poverty as a problem of "troubled" parenting. These views pervaded their interaction with parents and intersected with the regulatory influence of "policy technologies" to influence their practice within a context of austerity cuts. This limited practitioners' poverty sensitivity and their promotion of social justice. Therefore this paper concludes by critiquing the contribution which ECEC practitioners can make to addressing child poverty. Practical implications: – The findings suggest there may be a need for poverty proofing toolkits in the pre-school sector. Originality/value: – This paper provides a rare insight into how pre-school practitioners have engaged with, adopted and adapted assumptions about their role within policy discussion over child poverty and the promotion of social justice.